Continuity and change in the contemporary Pacific food system - Andrew, Neil L.; Allison, Edward H.; Brewer, Tom; Connell, John; Eriksson, Hampus; Eurich, Jacob; Farmery, Anna; Gephart, Jessica A.; Golden, Christopher D.; Herrero, Mario; Mapusua, Karen; Seto, Katherine; et al. (Elsevier, 2022)
The Pacific food system has become progressively more integrated into global food regimes. This integration has had impacts on availability and consumption of food, population health, and vulnerability to external drivers. We describe major elements of the contemporary food system to provide a foundation for analysis of food system transitions and public health outcomes. Although crop production has doubled in the last fifty years, it has not kept pace with population growth. This deficit is increasingly filled by imported foods, particularly staples, meat and sugar. The burden of malnutrition and poor health outcomes are increasingly apparent. We propose seeds for transitioning the Pacific food system to a hybrid form that supports historical continuity with healthy regionally-produced food.